Strategies for aquaculture development in a small Mediterranean island state: Malta - Agius C. (Aquaculture planning in Mediterranean countries, 1999)
In small island states of subtropical and tropical latitudes, shortage of space, fresh water as well as fierce competition for these precious resources from other economic sectors like tourism usually limits the potential for aquafarming to the marine environment. Moreover, these more lucrative sectors usually force aquaculture away from the prime foreshore sites out into the more exposed waters. Modern technology has come up with very practical and reliable, commercial scale cage structures for offshore sites. Increasingly sophisticated equipment such as for feeding, grading and harvesting have made life easier out at sea and have made possible the strict control over all activities concerned.
Workshop of the CIHEAM Network on Socio-economic and Legal Aspects of Aquaculture in the Mediterranean (SELAM), 1998/03/12-14, Tangiers (Morocco)